2012
DOI: 10.4161/cc.11.3.19116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and eradication of human glioma with tumor-targetingSalmonella typhimuriumin an orthotopic nude-mouse model

Abstract: (2012) Inhibition and eradication of human glioma with tumor-targeting Salmonellatyphimurium in an orthotopic nude-mouse model, Cell Cycle, 11:3,[628][629][630][631][632]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 28 publications
1
65
0
3
Order By: Relevance
“…Among these bacteria, S. enterica serovar Typhimurium strains have proven to be promising anticancer agents, which has led scientists to modify these bacteria to obtain strains with fewer side effects and improved therapeutic action [4,7,10-11,20,32-33]. Several studies have demonstrated that leu-arg auxotrophic S. enterica strain (A1-R) can effectively inhibit and in some cases even eradicate different types of primary and metastatic tumors when used as monotherapy in mouse models of prostate cancer [33-35], breast cancer [36][37][38], lung cancer [39,40], ovarian cancer [41,42], cervical cancer [43], pancreatic cancer [44][45][46][47][48], sarcoma [49][50][51] and glioma [52,53]. Recently, researchers have demonstrated that the S. enterica Typhimurium strain (STM) deficient for a zinc transporter operon can invade and proliferate in tumor cells, exerting therapeutic effect in the mammary adenocarcinoma mouse model by promoting an antitumor immune response [54].…”
Section: Discussionmentioning
confidence: 99%
“…Among these bacteria, S. enterica serovar Typhimurium strains have proven to be promising anticancer agents, which has led scientists to modify these bacteria to obtain strains with fewer side effects and improved therapeutic action [4,7,10-11,20,32-33]. Several studies have demonstrated that leu-arg auxotrophic S. enterica strain (A1-R) can effectively inhibit and in some cases even eradicate different types of primary and metastatic tumors when used as monotherapy in mouse models of prostate cancer [33-35], breast cancer [36][37][38], lung cancer [39,40], ovarian cancer [41,42], cervical cancer [43], pancreatic cancer [44][45][46][47][48], sarcoma [49][50][51] and glioma [52,53]. Recently, researchers have demonstrated that the S. enterica Typhimurium strain (STM) deficient for a zinc transporter operon can invade and proliferate in tumor cells, exerting therapeutic effect in the mammary adenocarcinoma mouse model by promoting an antitumor immune response [54].…”
Section: Discussionmentioning
confidence: 99%
“…An orthotopic mouse model of human glioblastoma was used to assess tumor growth in vivo. The surgical orthotopic implantation (SOI) method followed published procedures (14). U87-GFP, U87-H149, and U87-H4645 cells (5×10 6 ) were first subcutaneously injected in the flank of nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…Both B and T cells increase bacterial tumor inhibition and pretreatment with vaccines against bacteria increases the tumor-shrinking response [16,6466]. Bacterial therapy in mice and dogs has resulted in reduction of tumor volume, prevention of metastasis formation, and complete remission [12,15,51,6769]. …”
Section: Bacteria As Delivery Vectorsmentioning
confidence: 99%